Acid Free Oxidation and Simple Dispersion Method of MWCNT for High-Performance CFRP - Gerald Singer; Philipp Siedlaczek; Gerhard Sinn; Harald Rennhofer; Matej Mičušík; Maria Omastová; Miriam M. Unterlass; Josef Wendrinsky; Valeria Milotti; Filippo Fedi; Thomas Pichler; Helga C. Lichtenegger (Nanomaterials, 2018)
Carbon nanotubes (CNT) provide an outstanding property spectrum which can be used to improve a wide range of materials. However, the transfer of properties from the nanoscale to a macroscopic material is a limiting factor. Different approaches of functionalizing the surface of a CNT can improve the interaction with the surrounding matrix but is connected to difficult and expensive treatments, which are usually inconvenient for industrial applications. Here, a simple and eco-friendly method is presented for the oxidation of CNT, where hydrogen peroxide (H2O2) is the only chemical needed and no toxic emissions are released. Also, the extensive step of the incorporation of CNT to an epoxy matrix is simplified to an ultrasonic dispersion in the liquid hardener component. The effectiveness is proven by mechanical tests of produced CNT/CFRP and compared to a conventional processing route. The combination of those simple and cost efficient strategies can be utilized to produce multiscale composites with improved mechanical performance in an ecological and economical way.